Teoria democrática e instituições políticas: análise da representação de mulheres na Assembléia Legislativa de Minas Gerais(1999-2006). - Daniela Leandro Rezende (2008)
The present work sought to examine the impact of the election of women in Assembléia Legislativa de Minas Gerais. In other words, it seeks to investigate the impact of the presence of women in this institution, where the decision-making process takes place. Thus, itconsidered the 14ª and 15ª legislatures, between 1999 and 2002 and between 2003 and 2006, respectively. Underlying to this analysis, there is an effort to mediate the debates in contemporary democratic theory, sketched in the second and third chapters, and the empirical researches about Legislative power, specifically the ones that focus legislative behavior and process.